Theoretical and experimental investigation of protein crystal nucleation in pores and crevices - Nanev, Christo (IUCrJ, 2021)
The nucleation ability of pores is explained using the equilibration between the cohesive energy maintaining the integrity of a crystalline cluster and the destructive energy tending to tear it up. It is shown that to get 3D crystals it is vital to have 2D crystals nucleating in the pores first. By filling the pore orifice, the 2D crystal nuclei are more stable because their peripheries are protected from the destructive action of water molecules. Furthermore, the periphery of the 2D crystal is additionally stabilized as a result of its cohesion with the pore wall. The understanding provided by this study combining theory and experiment will facilitate the design of new nucleants.